Greece's economic odyssey: Persistent challenges and pathways forward - Evmorfia Makantasi; Helias Valentis (Economies, 2024)
Two years after the COVID-19 pandemic, the Greek economy seems to have overcome the turmoil of the pandemic crisis as well as that of the following energy crisis. Nevertheless, it would be wrong to assume that the Greek economy has returned to a sound state, since this was not really the case even before the pandemic. Furthermore, the anemic growth rates of the pre-pandemic period were followed by an equally weak average growth rate (including the impact of the pandemic), as some of the significant fundamental weaknesses of the Greek economy, which had accumulated over time and constituted the real origin of the Greek crisis, have not been properly addressed yet. This paper attempts a complete mapping of the current state of the Greek economy, offering an insight into the external and internal determinants affecting it.
Keywords: 330; development policy; eurozone; Greece; Greek competitiveness; Greek crisis; Greek debt; Greek economy; investment strategy